Rural Local Government System in Kazakhstan: Recent Issues - Zhumashov, Yerkebulan (International Review of Management and Marketing, 2016)
Nearly half of the country’s population still lives in rural areas, where the development of local government systems is an important issue, given that local government is the basis of political, social and civil changes in the rural community and in village transformation. Kazakhstan made a number of major changes in the lowest tier of the rural local government system toward democracy in 2012 to 2013. Within the framework of these changes, Kazakhstan provided for the election of local rural governors in 2013 for the first time in its history. Using the results of a nationwide survey among the rural population and analysing textual materials related to the topic, I reveal how satisfied rural respondents are with these changes and consider the problematic sides of a rural local government system that warrants further reforms. Keywords: rural local government system in Kazakhstan, rural management, local government, local democracy, decentralization, local self-government JEL Classifications: J54, K23, O18